Hubungan panjang berat dan faktor kondisi tiga jenis ikan yang tertangkap di perairan Kuala Gigieng, Aceh Besar, Provinsi Aceh - Mulfizar M; Zainal A. Muchlisin; Irma Dewiyanti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. The study of the lenght weight relationships and condition factors of the brackiswater fishes found in Kuala Gigeng was conducted. The objective of the present study was to evaluate the growth pattens and condition factor of the belanak (Mugil cephalus), seriding (Ambassis koopsii) and petek (Leiognathus fasciatus). The sampling was conducted for eight time on July 2011 by using gillnet and castnet. The results showed that the belanak (M. cephalus) and seriding (A. koopsii) have allometric negative growth patten, while the petek (L. fasciatus) has an allometric positive. In addition, the relative weight condition factor's was higher than 100. And the Fulton's condition factor were not different significantly among fishes. Indicating the condition of the Kuala Gigeng is relatively in good condition and support fish growth as well.Keywords. Allometric, Fulton's condition factor, fish relative weight, morphology